Interaksi Guru dengan Orang Tua Siswa Era Perang dan Damai di Aceh - Saifuddin Saifuddin (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2015)
The aim of the research is to analyze social interactions between teachers and parents during the era of war and peace in Aceh. This study employs qualitative method. During the war, the educational institution was one of the institutions which was affected badly. Social integration was so weak that interactions among parents of students, teachers and students were unstable. Within the war situation, social interactions were badly influenced hatred, suspicion, and revenge. The social interaction outside the school was contagious to that inside the school. But when the peace memorandum was signed on August 15, 2005, between the Indonesian government and Independence Aceh Movement (GAM), social interactions in schools began to show significant changes. When the war ended, people began to interact and socialize in good faith. Social interactions involving parents of students and teachers were also changing towards social stability and harmony so that they could inter-act without the feelings of fear, suspicion and revenge. Peace accord means that the enmity has significantly reduced. Hence, the teachers are effectively playing their fundamental role in teaching and socializing the younger generation of Acehnese.